Penerapan Media Gambar Terhadap Kemampuan Berpikir Kreatif Siswa Dalam Menulis Puisi - Rifa Nurdiana Arofah; Tsalitsatul Maulidah; Siti Aisah (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2021)
This study aims to determine the student’s thinking ability in writing. This research is quantitative research. This research focuses on the results of students writing related to the ability to think creatively in writing poetry, along with the factors that influence it. The research data was taken in June 2021. The research data was obtained using a one-group design. The research data was then calculated using SPSS 16 to determine whether the data taken in one class had an effect on students or not. The results of the first study were using pre-test data and for the second research results, namely post-test data. From these data, researchers can conclude the results that have been obtained in knowing student’s thinking abilities.